Laser plasma channel emission device, metal surface treatment method

CN117680825BActive Publication Date: 2026-10-27JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311793649.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2026-10-27
Estimated Expiration
2043-12-25

AI Technical Summary

Technical Problem

[0005]然而,在实际应用中,通常采用紧聚焦方式提高激光强度实现金属表面改性,限制了该种方法的工作距离;同时,紧聚焦条件下瑞利长度小,导致其无法在不规则的表面如曲面上实现激光改性

Benefits of technology

[0018]本发明还提供了一种金属表面处理方法,采用上述技术方案所述的激光等离子体通道发射装置,包括以下步骤:将所述激光等离子体通道发射装置发射的激光等离子体通道对金属表面进行扫描。在本发明中,激光脉冲本身与其在金属表面激发的等离子体波发生干涉效应,形成周期性微纳结构;等离子体通道长度远超过瑞利长度,同时其内部光强受光强钳制效应作用可保持几乎不变,使其能够对不规则表面如曲面等进行改性,工作距离与传统紧聚焦激光加工技术相比显著增加;使用了凹透镜和凸透镜组成的望远镜系统,能够调控产生等离子体通道的开始位置,因而可以方便地控制金属样品和聚焦系统的间距;该种增强耐腐蚀方法不依赖金属样品某一特有属性,具有普适性。因此,基于激光等离子体通道对金属进行表面处理的方法在推动金属材料在各种液体或潮湿等复杂环境中的使用,具有广阔的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117680825B_ABST
    Figure CN117680825B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of metal surface treatment, and particularly relates to a laser plasma channel emission device and a metal surface treatment method. The laser plasma channel emission device provided by the application is formed by the combined action of multiple nonlinear effects such as Kerr self-focusing and plasma defocusing of strong femtosecond laser in medium nonlinear propagation. The laser intensity in the plasma channel is about 100 TW / cm 2 , which is much larger than the laser damage threshold (10 TW / cm 2 ) of the metal surface, and can directly prepare a dense and thick passivation layer on the metal surface, thereby providing a prerequisite for improving corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal surface treatment technology, specifically relating to a laser plasma channel emitting device and a metal surface treatment method. Background Technology

[0002] Metallic materials are essential basic materials and important strategic resources for the development of the national economy, defense industry, and science and technology. However, metal corrosion is a very common phenomenon in nature, especially in complex environments such as liquids or moisture, including oceans, acid rain, and industrial wastewater, where corrosion is particularly severe, causing huge economic losses and restricting the application of metallic materials. Therefore, how to improve the corrosion resistance of metallic materials and further promote their application in various complex environments is a hot topic of great interest in this field.

[0003] Currently, various methods have been proposed to solve the corrosion problem of metallic materials, such as anti-corrosion coating and cathodic protection. Among them, laser surface modification has received widespread attention from the scientific and industrial communities due to its good processing quality, ease of automation, and environmental friendliness.

[0004] Wang et al. used nanosecond lasers to ablate 304 stainless steel to create a corrosion-resistant surface. Measurements in simulated seawater showed that the corrosion potential of this material increased by about 0.4V, and the corrosion rate decreased by about an order of magnitude (M. Wang et al. A contrastive investigation on the anticorrosive performance of stearicacid and fluoroalkylsilane-modified superhydrophobic surface in salt, alkali, and acid solution. Langmuir 36, 10279-10292 (2020)). Simultaneously, researchers proposed using a combination of nanosecond laser ablation and high-temperature annealing to improve the seawater corrosion resistance of metallic materials (magnesium-aluminum alloys). Results showed that the corrosion rate in simulated seawater decreased to one-fifteenth of the original sample (KM Mroczkowska et al. Anti-corrosion behavior of superwetting structured surfaces on Mg-9Al-1Znmagnesium alloy. Applied Surface Science 483, 1017-1026 (2019)).

[0005] However, in practical applications, a tight-focusing method is typically used to increase laser intensity for metal surface modification, which limits the working distance of this method. Furthermore, the small Rayleigh length under tight-focusing conditions prevents laser modification on irregular surfaces such as curved surfaces. Further improvements are needed to enhance the corrosion resistance of metallic materials based on nanosecond laser ablation techniques. Summary of the Invention

[0006] The purpose of this invention is to provide a laser plasma channel emitting device and a metal surface treatment method. The laser plasma channel generated by the laser plasma channel emitting device provided by this invention can perform surface treatment on metals, thereby further improving the corrosion resistance of the metals.

[0007] To achieve the above objectives, the present invention provides the following technical solution: The present invention provides a laser plasma channel emitting device, including a femtosecond laser amplifier 1; a first half-wave plate 2 and a polarizer 3 are arranged in the output optical path of the femtosecond laser amplifier 1; a laser frequency doubling system 4 and a dielectric film high-reflection mirror 5 are arranged in the output optical path of the polarizer 3; a second half-wave plate 6, a concave lens 7 and a convex lens 8 are arranged in the output optical path of the dielectric film high-reflection mirror 5. The convex lens 8 is fixed on a freely movable one-dimensional electrically controlled displacement platform 9.

[0008] Preferably, the laser pulse emitted by the femtosecond laser amplifier 1 has a center wavelength of 790~810nm, a pulse width of 30~1000fs, a repetition frequency of 0.1~10kHz, and a single pulse laser energy of 1~7mJ; the laser pulse is linearly polarized light with a horizontal polarization direction.

[0009] Preferably, the aperture of the first half-wave plate 2 is 25.4~38.1mm and the working wavelength is 690~1100nm.

[0010] Preferably, the working wavelength of the polarizer 3 is 750~850nm; When the laser pulse emitted by the femtosecond laser amplifier 1 irradiates the polarizer 3 at an incident angle of 72°, the polarization direction of the emitted light is vertically polarized.

[0011] Preferably, the working center wavelength of the dielectric film high-reflection mirror 5 is the same as the wavelength of the laser pulse output by the laser frequency doubling system 4; The operating wavelength of the second half-wave plate 6 is the same as the wavelength of the laser pulse output by the laser frequency doubling system 4; the aperture of the second half-wave plate 6 is 25.4~38.1mm.

[0012] Preferably, the focal length of the concave lens 7 is -200 to -40 cm.

[0013] Preferably, the focal length of the convex lens 8 is 40~200cm.

[0014] Preferably, the adjustment distance range of the one-dimensional electrically controlled displacement platform 9 is 50~400mm, and the displacement accuracy is 2.5μm; The present invention also provides a metal surface treatment method, using the laser plasma channel emitting device described above, comprising the following steps: The laser plasma channel emitted by the laser plasma channel emitting device scans the metal surface.

[0015] Preferably, the scanning speed is 0.5~5mm / s and the scanning interval is 50~500μm.

[0016] This invention provides a laser plasma channel emitting device, including a femtosecond laser amplifier 1; a first half-wave plate 2 and a polarizer 3 are arranged in the output optical path of the femtosecond laser amplifier 1; a laser frequency doubling system 4 and a dielectric film high-reflection mirror 5 are arranged in the output optical path of the polarizer 3; a second half-wave plate 6, a concave lens 7 and a convex lens 8 are arranged in the output optical path of the dielectric film high-reflection mirror 5; the convex lens 8 is fixed on a freely movable one-dimensional electrically controlled displacement platform 9.

[0017] The laser plasma channel emitting device provided by this invention is formed by the combined effects of multiple nonlinear effects, such as Kerr self-focusing and plasma defocusing, during the nonlinear propagation of a strong femtosecond laser in a medium. The laser intensity within the plasma channel is approximately 100 TW / cm². 2 The magnitude is much greater than the laser damage threshold for metal surfaces (10 TW / cm). 2 It can directly prepare a dense and thick passivation layer on the metal surface, providing a prerequisite for improving corrosion resistance.

[0018] This invention also provides a metal surface treatment method using the laser plasma channel emitting device described above, comprising the following steps: scanning the metal surface with a laser plasma channel emitted by the laser plasma channel emitting device. In this invention, the laser pulse itself interferes with the plasma wave excited on the metal surface, forming a periodic micro / nano structure; the plasma channel length far exceeds the Rayleigh length, and its internal light intensity remains almost constant due to the light intensity clamping effect, enabling modification of irregular surfaces such as curved surfaces. The working distance is significantly increased compared to traditional tightly focused laser processing technology; a telescope system composed of concave and convex lenses is used, which can control the starting position of the plasma channel generation, thus conveniently controlling the distance between the metal sample and the focusing system; this enhanced corrosion resistance method does not rely on any specific property of the metal sample and has universality. Therefore, the method of surface treatment of metals based on laser plasma channels has broad application prospects in promoting the use of metal materials in various complex environments such as liquids or humidity. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the device for surface treatment of metal based on laser plasma channel according to the present invention, wherein 1 is a femtosecond laser amplifier, 2 is a first half-wave plate, 3 is a polarizer, 4 is a laser frequency doubling system, 5 is a dielectric film high reflection mirror, 6 is a second half-wave plate, 7 is a concave lens, 8 is a convex lens, 9 is a one-dimensional electrically controlled displacement platform, and 10 is a two-dimensional electrically controlled sample stage. Figure 2 The anodic and cathodic polarization curves of the surface-treated 304 stainless steel obtained in Example 1 are shown in simulated seawater. Figure 3 The anodic and cathodic polarization curves of the surface-treated 304 stainless steel obtained in Example 1 in hydrochloric acid solution with a pH of 2 are shown. Figure 4 The anodic and cathodic polarization curves of the surface-treated 304 stainless steel obtained in Example 1 in a sodium hydroxide solution with a pH of 12 are shown. Figure 5 The anodic and cathodic polarization curves of surface-treated 1A99 industrial pure aluminum obtained in Example 2 are shown in simulated seawater. Figure 6 The anodic and cathodic polarization curves of the surface-treated TC4 titanium alloy obtained in Example 3 are shown in simulated seawater. Detailed Implementation

[0020] The present invention provides a laser plasma channel emitting device, including a femtosecond laser amplifier 1; a first half-wave plate 2 and a polarizer 3 are arranged in the output optical path of the femtosecond laser amplifier 1; a laser frequency doubling system 4 and a dielectric film high-reflection mirror 5 are arranged in the output optical path of the polarizer 3; a second half-wave plate 6, a concave lens 7 and a convex lens 8 are arranged in the output optical path of the dielectric film high-reflection mirror 5. The convex lens 8 is fixed on a freely movable one-dimensional electrically controlled displacement platform 9.

[0021] In this invention, the center wavelength of the laser pulse emitted by the femtosecond laser amplifier 1 is preferably 790~810nm, the pulse width is preferably 30~1000fs, the repetition frequency is preferably 0.1~10kHz, and the single pulse laser energy is preferably 1~7mJ; the laser pulse is preferably linearly polarized light, and the polarization direction is preferably horizontal.

[0022] In this invention, the aperture of the first half-wave plate 2 is preferably 25.4~38.1mm, and the operating wavelength is preferably 690~1100nm.

[0023] In this invention, the operating wavelength of the polarizer 3 is preferably 750~850nm. In this invention, when the laser pulse emitted by the femtosecond laser amplifier 1 irradiates the polarizer 3 at an incident angle of 72°, the polarization direction of the emitted light is preferably vertically polarized.

[0024] In this invention, the first half-wave plate 2 and the polarizer 3 form a laser pulse energy adjustment system. By rotating the first half-wave plate 2 to change the polarization direction of the laser pulse, the energy of the laser reflected by the polarizer 3 can be adjusted.

[0025] In this invention, the laser frequency doubling system 4 preferably converts the laser pulses output by the femtosecond laser amplifier 1 into frequency-second or frequency-third harmonic lasers. In a specific embodiment of this invention, the laser frequency doubling system 4 preferably converts the laser pulses with a wavelength of 790-810 nm output by the femtosecond laser amplifier 1 into frequency-second or frequency-third harmonic near-ultraviolet lasers; the wavelength of the frequency-second harmonic near-ultraviolet laser pulses is preferably 395-405 nm; and the wavelength of the frequency-third harmonic near-ultraviolet laser pulses is preferably 263-270 nm. In this invention, the laser frequency doubling system 4 provides laser pulses of different wavelengths for the subsequent generation of the plasma channel.

[0026] In this invention, the working center wavelength of the dielectric film high-reflection mirror 5 is preferably the same as the wavelength of the laser pulse output by the laser frequency doubling system 4.

[0027] In this invention, the operating wavelength of the second half-wave plate 6 is preferably the same as the wavelength of the laser pulse output by the laser frequency doubling system 4. In this invention, the aperture of the second half-wave plate 6 is preferably 25.4~38.1 mm. In this invention, the first half-wave plate 6 is used to change the polarization direction of the incident laser pulse.

[0028] In this invention, the focal length of the concave lens 7 is preferably -200 to -40 cm. In this invention, the focal length of the convex lens 8 is preferably 40 to 200 cm. In this invention, the concave lens 7 and the convex lens 8 together constitute a telescope system, and a laser plasma channel is generated after the laser pulse passes through.

[0029] In this invention, the convex lens 8 is fixed on a freely movable one-dimensional electrically controlled displacement platform 9. The adjustment distance range of the one-dimensional electrically controlled displacement platform 9 is preferably 50~400mm, and the displacement accuracy is preferably 2.5μm. The one-dimensional electrically controlled displacement platform 9 controls the generation position of the laser plasma channel by changing the relative position between the convex lens 8 and the concave lens 7 through software programs.

[0030] The present invention also provides a metal surface treatment method, using the laser plasma channel emitting device described above, comprising the following steps: The laser plasma channel emitted by the laser plasma channel emitting device scans the metal surface.

[0031] Before the scanning, the present invention preferably includes cleaning and drying the metal; the cleaning preferably includes ultrasonic cleaning in acetone, ethanol and deionized water in sequence; the ultrasonic cleaning time in acetone, ethanol and deionized water is preferably 15 min each. In the present invention, the drying process is preferably: drying in a constant temperature drying oven at 80°C for 15 min.

[0032] This invention does not specifically limit the type of metal used; any metal well-known to those skilled in the art can be used. In this invention, the metal is preferably fixed on a freely movable two-dimensional electrically controlled sample stage 10. The relative distance between the concave lens 7 and the convex lens 8 is changed by controlling the position of the one-dimensional electrically controlled displacement platform 9 through software, thereby changing the position of the laser plasma channel that interacts with the metal sample. The two-dimensional electrically controlled sample stage 10 is moved by software, and the surface of the metal sample is scanned using the laser plasma channel.

[0033] In this invention, the two-dimensional electrically controlled sample stage 10 is preferably controlled by software program to move in the xy plane perpendicular to the transmission direction of the laser plasma channel. The adjustment distance range in both the x and y directions is preferably 0.05~200mm, the displacement accuracy is preferably 2.5μm, and the displacement speed range is preferably 0.1~7.5mm / s.

[0034] In this invention, the scanning speed is preferably 0.5~5mm / s, and the scanning spacing is preferably 50~500μm.

[0035] In this invention, the scanning process is preferably as follows: Step 1: Set the technical parameters of the femtosecond laser amplifier 1; Step 2: Rotate the first half-wave plate 2 to continuously change the laser pulse energy reflected by the galvanometer 3; Step 3: Use the laser frequency doubling system 4 to obtain laser pulses with different center wavelengths; Step 4: After passing through the dielectric film reflector 5, use a laser power meter to measure the ultrafast laser pulse power to obtain the single pulse energy; Step 5: Rotate the second half-wave plate 6 to adjust the polarization direction of the laser pulse; Step 6: After the laser pulse passes through the concave lens 7 and the convex lens 8, a laser plasma channel is generated to scan the metal fixed on the two-dimensional electrically controlled sample stage 10.

[0036] Following the scanning, the present invention preferably includes cleaning, drying, and post-treatment of the scanned metal; the cleaning preferably includes ultrasonic cleaning sequentially in acetone, ethanol, and deionized water; the ultrasonic cleaning time in acetone, ethanol, and deionized water is preferably 15 min each. In the present invention, the drying process is preferably performed in a constant temperature drying oven at 80°C for 15 min. In the present invention, the post-treatment preferably includes heat treatment or chemical treatment. In the present invention, the heat treatment temperature is preferably 120~400°C, and the holding time is preferably 2 h or more. In the present invention, the chemical treatment process is preferably performed by placing the dried metal in a 1.2 wt% 1H,1H,2H,2H-perfluorodecyltrichlorosilane ethanol solution for 12 h. In the present invention, the corrosion resistance of the metal can be further improved through heat treatment or chemical treatment.

[0037] To further illustrate the present invention, a laser plasma channel emitting device and a metal surface treatment method provided by the present invention will be described in detail below with reference to the accompanying drawings and embodiments, but these should not be construed as limiting the scope of protection of the present invention.

[0038] Example 1 Surface treatment of 304 stainless steel; The 304 stainless steel sample used was 10×10mm in size. 2The thickness is 0.5 mm. The 304 stainless steel sample was ultrasonically cleaned in acetone, ethanol and deionized water in sequence, and cleaned in each liquid for 15 min. The cleaned sample was then placed in a constant temperature drying oven at 80℃ for 15 min. The technical parameters of the femtosecond laser amplifier 1 are set (center wavelength of 800nm, pulse width of 45fs, repetition frequency of 1kHz, and single pulse energy of 2mJ). The plasma channel formed by the laser plasma channel emitting device is used to modify the surface of 304 stainless steel. The two-dimensional electrically controlled sample stage 10 is used to continuously change the interaction position between the laser plasma channel and the sample surface to achieve full coverage scanning of the sample surface. The scanning speed is 0.5mm / s and the scanning interval is 0.1mm. The scanned 304 stainless steel sample was ultrasonically cleaned in acetone, ethanol and deionized water in sequence, for 15 min in each liquid; the cleaned sample was then placed in an 80℃ constant temperature drying oven for 15 min. The dried 304 stainless steel sample was placed on a piece of filter paper and heated together in a heating oven at 150°C for 2 hours to obtain surface-treated 304 stainless steel.

[0039] Example 2 Surface treatment of 1A99 industrial pure aluminum sample; The procedure was performed as described in Example 1, except that the scanning speed of the laser plasma channel was replaced with 1 mm / s.

[0040] Example 3 Surface treatment was performed on the TC4 titanium alloy sample; The procedure was performed as described in Example 1, except that the scanning speed of the laser plasma channel was replaced with 1 mm / s.

[0041] Performance testing The corrosion resistance of the 304 stainless steel with the surface treatment obtained in Example 1 was tested; Untreated 304 stainless steel was used as a blank control. The blank control sample was cleaned and dried only according to the pre-scanning pretreatment method in Example 1. (1) Electrochemical test of seawater corrosion resistance Electrochemical testing mainly includes polarization curves of the anode and cathode, as well as electrochemical impedance spectroscopy.

[0042] Figure 2 Figure (a) shows the cathodic polarization curves of the surface-treated 304 stainless steel (square dots) obtained in Example 1 and the blank control sample (round dots) in simulated seawater. It can be seen that the polarization voltage of the surface-treated 304 stainless steel obtained in Example 1 is 0.243V, and the polarization current density is 2.272×10⁻⁶.-11 A / cm 2 The calculated corrosion rate is 2.676 × 10⁻⁶. -7 mm / year. The polarization voltage of the blank control sample was -0.164V, and the polarization current density was 1.735×10 mm / year. -6 A / cm 2 The calculated corrosion rate is 2.044 × 10⁻⁶. -2 mm / year.

[0043] Figure 2 Figure (b) shows the anodic polarization curves of the surface-treated 304 stainless steel (square dots) obtained in Example 1 and the blank control sample (round dots) in simulated seawater. It can be seen that the polarization voltage of the surface-treated 304 stainless steel obtained in Example 1 is 0.212V, and the polarization current density is 3.242×10⁻⁶. -11 A / cm 2 The calculated corrosion rate was 3.836 × 10⁻⁶. -7 mm / year. The polarization voltage of the blank control sample was -0.175V, and the polarization current density was 2.238 × 10⁻⁶ mm / year. -6 A / cm 2 The corrosion rate obtained from this is 2.653 × 10⁻⁶. -2 mm / year.

[0044] The above results indicate that the corrosion rate of the surface-treated 304 stainless steel obtained in Example 1 is 5 orders of magnitude lower than that of the blank control sample, demonstrating excellent corrosion resistance.

[0045] (2) Electrochemical test of acid and alkali corrosion resistance Figure 3 Figure (a) shows the cathodic polarization curves of the surface-treated 304 stainless steel (square dots) obtained in Example 1 and the blank control sample (round dots) in hydrochloric acid solution with a pH of 2. It can be seen that the polarization voltage of the surface-treated 304 stainless steel obtained in Example 1 is 0.163V, and the polarization current density is 2.876×10⁻⁶. -11 A / cm 2 The calculated corrosion rate is 3.388 × 10⁻⁶. -7 mm / year. The polarization voltage of the blank control sample was -0.172V, and the polarization current density was 5.059×10 mm / year. -6 A / cm 2 The calculated corrosion rate is 5.959 × 10⁻⁶. -2 mm / year.

[0046] Figure 3Figure (b) shows the anodic polarization curves of the surface-treated 304 stainless steel (square dots) obtained in Example 1 and the blank control sample (round dots) in hydrochloric acid solution with a pH of 2. It can be seen that the polarization voltage of the surface-treated 304 stainless steel obtained in Example 1 is 0.153V, and the polarization current density is 3.049×10⁻⁶. -11 A / cm 2 The corrosion rate obtained from this is 3.592 × 10⁻⁶. -7 mm / year. The polarization voltage of the blank control sample was -0.189V, and the polarization current density was 5.799×10 mm / year. -6 A / cm 2 The corrosion rate obtained from this is 6.808 × 10⁻⁶. -2 mm / year.

[0047] Figure 4 Figure (a) shows the cathodic polarization curves of the surface-treated 304 stainless steel (square dots) obtained in Example 1 and the blank control sample (round dots) in a sodium hydroxide solution with a pH of 12. It can be seen that the polarization voltage of the surface-treated 304 stainless steel obtained in Example 1 is 0.542V, and the polarization current density is 5.712×10⁻⁶. -11 A / cm 2 The corrosion rate obtained from this is 6.729 × 10⁻⁶. -7 mm / year. The polarization voltage of the blank control sample was -0.114V, and the polarization current density was 1.742 × 10⁻⁶ mm / year. - 7 A / cm 2 Based on this, the corrosion rate was calculated to be 2.052 × 10⁻⁶. -3 mm / year.

[0048] Figure 4 Figure (b) shows the anodic polarization curves of the surface-treated 304 stainless steel (square dots) obtained in Example 1 and the blank control sample (round dots) in a sodium hydroxide solution with a pH of 12. It can be seen that the polarization voltage of the surface-treated 304 stainless steel obtained in Example 1 is 0.50V, and the polarization current density is 4.242×10⁻⁶. -11 A / cm 2 The corrosion rate obtained from this is 4.997 × 10⁻⁶. -7 mm / year. The polarization voltage of the blank control sample was -0.132V, and the polarization current density was 2.952×10 mm / year. - 7 A / cm 2 The corrosion rate obtained from this is 3.478 × 10⁻⁶. -3 mm / year.

[0049] In summary, by comparing the surface-treated 304 stainless steel obtained in Example 1 with the blank control sample, it can be seen that the seawater corrosion resistance rate of the surface-treated 304 stainless steel obtained by the present invention is reduced by 5 orders of magnitude compared with the blank control sample, and the self-corrosion potential increases by 0.399V, causing the corrosion rate of the stainless steel surface in seawater to decrease from the original 0.02mm / year to 0.3nm / year. Simultaneously, it can be seen that the acid corrosion resistance rate of the surface-treated 304 stainless steel obtained by the present invention is reduced by 5 orders of magnitude compared with the blank control sample, and the self-corrosion potential increases by 0.335V, causing the corrosion rate of the stainless steel surface in acidic solutions to decrease from the original 0.03mm / year to 0.4nm / year. Furthermore, it can be seen that the alkali corrosion resistance rate of the surface-treated 304 stainless steel obtained by the present invention is reduced by 4 orders of magnitude compared with the blank control sample, and the self-corrosion potential increases by 0.656V, causing the corrosion rate of the stainless steel surface in alkaline solutions to decrease from the original 0.002mm / year to 0.7nm / year. Therefore, the surface treatment method provided by the present invention can significantly enhance the resistance of 304 stainless steel samples to seawater and acid and alkali corrosion, and has important value in promoting the application of metal materials in liquid or humid environments.

[0050] Test Example 2 The corrosion resistance of the surface-treated 1A99 industrial pure aluminum obtained in Example 2 was tested; 1A99 industrial pure aluminum without surface treatment was used as a blank control. The blank control sample was only cleaned and dried according to the pre-scanning pretreatment method in Example 2. Electrochemical tests for resistance to seawater corrosion: Figure 5 In Figure (a), the cathodic polarization curves of the surface-treated 1A99 industrial pure aluminum (square) and the blank control sample (circular) obtained in Example 2 are shown in simulated seawater. It can be seen that the polarization voltage of the surface-treated 1A99 industrial pure aluminum obtained in Example 2 is -1.106V, and the polarization current density is 3.81×10⁻⁶V. -12 A / cm 2 The polarization voltage of the blank control sample was -0.746V, and the polarization current density was 1.047 × 10⁻⁶. -5 A / cm 2 .

[0051] Figure 5 Figure (b) shows the anodic polarization curves of the surface-treated 1A99 industrial pure aluminum (square) obtained in Example 2 and the blank control sample (circular) in simulated seawater. It can be seen that the surface-treated 1A99 industrial pure aluminum obtained in Example 2 has a polarization voltage of -0.904V and a polarization current density of 1.816×10⁻⁶. -12A / cm 2 The polarization voltage of the blank control sample was -0.745V, and the polarization current density was 2.511 × 10⁻⁶. -5 A / cm 2 The corrosion rate of a metal is proportional to its polarization current density. The above results indicate that the corrosion rate of the surface-treated 1A99 industrial pure aluminum obtained in Example 2 is 7 orders of magnitude lower than that of the blank control sample.

[0052] In summary, the seawater corrosion resistance rate of the surface-treated 1A99 industrial pure aluminum obtained by this invention is reduced by seven orders of magnitude compared to the blank control sample. Therefore, the method of this invention can significantly enhance the seawater corrosion resistance of 1A99 industrial pure aluminum samples.

[0053] Test Example 3 The corrosion resistance of the TC4 titanium alloy with surface treatment obtained in Example 3 was tested; TC4 titanium alloy without surface treatment was used as a blank control. The blank control sample was only cleaned and dried according to the pre-scanning pretreatment method in Example 3. Electrochemical tests for resistance to seawater corrosion: Figure 6 Figure (a) shows the cathodic polarization curves of the surface-treated TC4 titanium alloy (square) obtained in Example 3 and the blank control sample (circular) in simulated seawater. It can be seen that the polarization voltage of the surface-treated TC4 titanium alloy obtained in Example 3 is 0.137V, and the polarization current density is 5.464×10⁻⁶. -10 A / cm 2 The polarization voltage of the blank control sample was -0.145V, and the polarization current density was 2.433 × 10⁻⁶. -6 A / cm 2 .

[0054] Figure 6 Figure (b) shows the anodic polarization curves of the surface-treated TC4 titanium alloy (square) obtained in Example 3 and the blank control sample (circular) in simulated seawater. It can be seen that the polarization voltage of the surface-treated TC4 titanium alloy obtained in Example 3 is 0.109V, and the polarization current density is 8.979×10⁻⁶. -10 A / cm 2 The polarization voltage of the blank control sample was -0.175V, and the polarization current density was 3.591×10⁻⁶. -6 A / cm 2 The above results indicate that the corrosion rate of the surface-treated TC4 titanium alloy obtained in Example 2 is four orders of magnitude lower than that of the blank control sample.

[0055] In summary, the corrosion rate of the TC4 titanium alloy surface treated by this invention is reduced by four orders of magnitude compared to the blank control sample. Therefore, the method of this invention can significantly enhance the seawater corrosion resistance of TC4 titanium alloy samples.

[0056] As can be seen from the above test examples, the laser plasma channel-based surface treatment of metals provided by this invention has a significant improvement effect, and has great application potential and broad development prospects in promoting the use of metal materials in complex environments such as liquids or humid environments.

[0057] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A laser plasma channel emitting device, characterized in that, The system includes a femtosecond laser amplifier (1); a first half-wave plate (2) and a polarizer (3) are provided on the output optical path of the femtosecond laser amplifier (1); a laser frequency doubling system (4) and a dielectric film high-reflection mirror (5) are provided on the output optical path of the polarizer (3); a second half-wave plate (6), a concave lens (7) and a convex lens (8) are provided on the output optical path of the dielectric film high-reflection mirror (5). The working center wavelength of the dielectric film high-reflection mirror (5) is the same as the wavelength of the laser pulse output by the laser frequency doubling system (4); the working wavelength of the second half-wave plate (6) is the same as the wavelength of the laser pulse output by the laser frequency doubling system (4); The convex lens (8) is fixed on a freely movable one-dimensional electrically controlled displacement platform (9); The laser plasma channel emitting device is used for metal surface treatment; The plasma channel length exceeds the Rayleigh length.

2. The laser plasma channel emitting device according to claim 1, characterized in that, The laser pulse emitted by the femtosecond laser amplifier (1) has a center wavelength of 790~810nm, a pulse width of 30~1000fs, a repetition frequency of 0.1~10kHz, and a single pulse laser energy of 1~7mJ; the laser pulse is linearly polarized light with a horizontal polarization direction.

3. The laser plasma channel emitting device according to claim 1, characterized in that, The aperture of the first half-wave plate (2) is 25.4~38.1mm and the working wavelength is 690~1100nm.

4. The laser plasma channel emitting device according to claim 1, characterized in that, The working wavelength of the polarizer (3) is 750~850nm; When the laser pulse emitted by the femtosecond laser amplifier (1) irradiates the polarizer (3) at an incident angle of 72°, the polarization direction of the emitted light is vertically polarized.

5. The laser plasma channel emitting device according to claim 1, characterized in that, The aperture of the second half-wave plate (6) is 25.4~38.1mm.

6. The laser plasma channel emitting device according to claim 1, characterized in that, The focal length of the concave lens (7) is -200~-40cm.

7. The laser plasma channel emitting device according to claim 1, characterized in that, The focal length of the convex lens (8) is 40~200cm.

8. The laser plasma channel emitting device according to claim 1, characterized in that, The adjustment range of the one-dimensional electrically controlled displacement platform (9) is 50~400mm, and the displacement accuracy is 2.5μm.

9. A method for treating metal surfaces, characterized in that, The laser plasma channel emitting device according to any one of claims 1 to 8 includes the following steps: The laser plasma channel emitted by the laser plasma channel emitting device scans the metal surface.

10. The metal surface treatment method according to claim 9, characterized in that, The scanning speed is 0.5~5mm / s, and the scanning interval is 50~500μm.

Citation Information

Patent Citations

  • Method for preparing anti-corrosion structure on irregular metal surface remotely, rapidly and in large area

    CN114799528A

  • Method for realizing remote controllable femtosecond laser filament ignition by using telescope focusing system

    CN115224575A